2016
DOI: 10.1136/bmjopen-2015-011016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an SMS advice programme on maternal and newborn health in rural China: study protocol for a quasi-randomised controlled trial

Abstract: IntroductionExpectant mothers in low-income and middle-income countries often lack access to vital information about pregnancy, preparation for birth and best practices when caring for their newborn. Innovative solutions are needed to bridge this knowledge gap and dramatically improve maternal and neonatal health in these settings. This study aims to evaluate the impact of an innovative text messaging intervention on maternal and neonatal health outcomes.Methods and analysisThis study offers expectant mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…To address this issue, we designed and implemented a quasi-randomized controlled trial, the Newborn Health Project in rural China, to determine if and how an innovative SMS intervention providing educational information via texts to pregnant women in China might lead to maternal and child health outcomes. A more in-depth discussion of the literature and the study protocol has been reported previously [18]. Our study will add to the literature that maternal health education via cell phone text messages could greatly prevent the occurrence of inappropriate weight for gestational age, particularly on the macrosomic end of the spectrum.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…To address this issue, we designed and implemented a quasi-randomized controlled trial, the Newborn Health Project in rural China, to determine if and how an innovative SMS intervention providing educational information via texts to pregnant women in China might lead to maternal and child health outcomes. A more in-depth discussion of the literature and the study protocol has been reported previously [18]. Our study will add to the literature that maternal health education via cell phone text messages could greatly prevent the occurrence of inappropriate weight for gestational age, particularly on the macrosomic end of the spectrum.…”
Section: Introductionmentioning
confidence: 69%
“…This study was approved by the Ethics Committee of the School of Medicine at Xi'an Jiaotong University on 18 January 2013 and an updated version was approved on May 2016 (Approval number: 2016-392). In addition, this study was registered at clinicaltrials.gov (NCT02037087), and the protocol has been published previously [18]. Power calculation to determine sample size was presented in the published protocol [18].…”
Section: Pre-trial Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The study involved various message categories emphasizing adherence to positive behaviours including reminders for prenatal visits, facility delivery and healthy lifestyles (nutrition and physical activity). Study findings imply that a mHealth intervention using messages can be more effective if participants have a chance to interact with a medical practitioner to discuss the messages for reinforcement and confirmation [34].…”
Section: Resultsmentioning
confidence: 99%